PUSAT WISATA KULINER BERBASIS KEARIFAN LOKAL DI PESISIR PANTAI SERANGAN - Ni Wayan Mega Sari Apri Yani; Ida Ayu Etsa Pracintya; I Made Trisna Semara; Ni Luh Helen Susani (LPSDI Bina Patria, 2024)
Serangan Village has been designated as a tourism village, yet the community lacks awareness of the importance of tourism and has not optimized its tourism potential. Additionally, its development remains conventional. Therefore, improvements are necessary by reorganizing the area to establish a new tourism center. A culinary tourism center is deemed highly suitable for Serangan Village as it promotes local culinary specialties as tourism products while preserving local cultural values. This study aims to design a culinary tourism center model using SWOT analysis and two-dimensional design visualization. The research employed a qualitative approach